Splitting at the seams: Extensive Stanford Type A aortic dissection - Fan, Jerry; Lee, Mary; Lewis, Austin (SA Heart Journal, 2019)
We present a rare case of extensive Stanford Type A aortic dissection extending from the ascending aorta superiorly to the carotids and inferiorly to the infra-renal abdominal aorta. A 34-year-old male with history of hypertension and tobacco use presents with chest pain, dyspnoea, slurred speech and altered mental status. Chest radiograph showed no mediastinal widening. CT head showed multiple sub-cortical infarcts and CT chest showed mild dilation of the thoracic aorta but no dissection. He subsequently reported bilateral lower extremity numbness and weakness and was intubated for hypoxic respiratory failure. A CT scan of the chest showed extensive Type A aortic dissection. He underwent emergent surgical intervention but due to the extensive dissection and blood loss, he ultimately expired.